2015
DOI: 10.1128/iai.03079-14
|View full text |Cite
|
Sign up to set email alerts
|

Design of Glycoconjugate Vaccines against Invasive African Salmonella enterica Serovar Typhimurium

Abstract: dNontyphoidal salmonellae, particularly Salmonella enterica serovar Typhimurium, are a major cause of invasive disease in Africa, affecting mainly young children and HIV-infected individuals. Glycoconjugate vaccines provide a safe and reliable strategy against invasive polysaccharide-encapsulated pathogens, and lipopolysaccharide (LPS) is a target of protective immune responses. With the aim of designing an effective vaccine against S. Typhimurium, we have synthesized different glycoconjugates, by linking O-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 54 publications
1
77
0
Order By: Relevance
“…Typhimurium D23580 isolate (33), which can be attributed to the phage-borne family 2 gtr operon that is expressed in this specific strain (21). However, detailed analyses in the context of the host, disease, and serovars are needed to further clarify the impact of O-antigen acetylation and glucosylation (36, 37). …”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium D23580 isolate (33), which can be attributed to the phage-borne family 2 gtr operon that is expressed in this specific strain (21). However, detailed analyses in the context of the host, disease, and serovars are needed to further clarify the impact of O-antigen acetylation and glucosylation (36, 37). …”
Section: Discussionmentioning
confidence: 99%
“…Given its effect on serotype, glucosylation is an important consideration in vaccine strategies (41,42). Molecular modeling studies have established that glucosylation alters the conformation of Shigella O-antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium OPS is optimally immunogenic, however, the very long chain form was a poor vaccine hapten when end‐linked (Rondini et al . ). It has also been previously shown that the short‐chain COPS from S .…”
Section: Discussionmentioning
confidence: 97%